2018
DOI: 10.1111/imj.13797
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis: a Hunter New England perspective

Abstract: IE in the HNELHD affects a relatively young cohort of patients and is associated with a high mortality. Outcomes could be improved by implementation of a multidisciplinary team approach and inpatient cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
2
4
1
Order By: Relevance
“…We found that patients with S. aureus bacteraemia tended to be younger, with a higher likelihood of intravenous drug use, compared to those with an E. faecalis bacteraemia, who were older and more likely to have a PPM in situ or prosthetic valve endocarditis. This is consistent with previous reports of a bimodal distribution in age of patients with infective endocarditis 12 . Only 15% of our patients were intravenous drug users, compared to a rate of 30% reported in an interstate cohort 15 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found that patients with S. aureus bacteraemia tended to be younger, with a higher likelihood of intravenous drug use, compared to those with an E. faecalis bacteraemia, who were older and more likely to have a PPM in situ or prosthetic valve endocarditis. This is consistent with previous reports of a bimodal distribution in age of patients with infective endocarditis 12 . Only 15% of our patients were intravenous drug users, compared to a rate of 30% reported in an interstate cohort 15 .…”
Section: Discussionsupporting
confidence: 93%
“…We also found older age, ICU admission prior to or without subsequent cardiac surgery and severe LVEF impairment as other independent predictors of mortality. Increased age, LVEF impairment and inotrope requirement (a proxy for ICU admission) have similarly been reported in other cohorts as predictors of mortality 12,13 . Other studies have also found prosthetic valve endocarditis, S. aureus bacteraemia and increased vegetation size as predictors of mortality, which was not the case in our cohort 13,14 .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The last but not the least was the high rate of surgical treatment. Better prognosis had been reported in IE patients with a higher rate of valvular surgery [20,21].…”
Section: Discussionmentioning
confidence: 93%